Supply Chain Management and Performance of Juhel Pharmaceutical Company, Awka, Anambra State, Nigeria - Florence Okeke (Ph.D), Adaora (Research Parks Publishers, 2025)
This study examines the effect of supply chain management on performance of Juhel pharmaceutical company, Awka, Anambra State, Nigeria. The study adopted survey research design. The population of the study comprised sixty-seven (67) employees of Juhel Pharmaceutical Company, Awka, Anambra State. Questionnaire was employed as the instrument of data collection. The study found that strategic supplier partnership, customer relationship and the level and quality of information sharing have significant effect on the performance of Juhel pharmaceutical company. The study concluded that supply chain management has significant positive effect on performance. The study recommended that companies should consider adopting supply chain practices particularly strategic supplier partnership fully as the potential benefits to be realized are enormous compared to the initial and operational cost of implementing the practice.